Evaluasi Medication Error Pada Resep Pasien Anak Di Apotek Sinar Baru 2023 - Moniciram, Wyndha (Universitas Pahlawan Tuanku Tambusai, 2024)
Introduction: The United States Food and Drug Administration (FDA) receives more than 100,000 reports of medication errors each year that occur in pharmacies, hospitals and patients' homes. Based on previous research conducted by Bates (Bates, 1995), it showed that the highest ranking of medication errors was in the prescribing phase (49%), the prescribing error phase (26%), and the dispensing phase (25%). Objectives: toknow the prevalence of medication errors in the prescribing phase and the transcribing phase in prescriptions for pediatric patients at the Sinar Baru Pharmacy in 2023 and to find out The relationship between pediatric patient characteristics and the incidence of Medication Error. Method: This research is a non-experimental research with quantitative methods and a descriptive approach which carried out data collection retrospectively by looking at data/prescriptions from pediatric patients. Results and Conclusions: in the medication error study in the prescribing phase, there were 100% prescriptions for which there was no doctor's SIP, followed by 100% of no gender, 3% of no doctor's initials, and 2% of no prescription request date. Then, in the transcribing phase it was incomplete/unclear/no medical records with the number of events being 2 with a percentage of 2%. There is no relationship between medication errors and the characteristics of pediatric patient prescriptions where the results show > 0.05. Keywords : Medication Error, Prescribing Phase, Transcribing Phas